Pharmacological and Genetic Suppression of VDAC1 Alleviates the Development of Mitochondrial Dysfunction in Endothelial and Fibroblast Cell Cultures upon Hyperglycemic Conditions - Konstantin N. Belosludtsev; Dmitriy A. Serov; Anna I. Ilzorkina; Vlada S. Starinets; Mikhail V. Dubinin; Eugeny Yu. Talanov; Maxim N. Karagyaur; Alexandra L. Primak; Natalia V. Belosludtseva (MDPI AG, 2023)
Prolonged hyperglycemia related to diabetes and its complications leads to multiple cellular disorders, the central one being the dysfunction of mitochondria. Voltage-dependent anion channels (VDAC) of the outer mitochondrial membrane control the metabolic, ionic, and energy cross-talk between mitochondria and the rest of the cell and serve as the master regulators of mitochondrial functions. Here, we have investigated the effect of pharmacological suppression of VDAC1 by the newly developed inhibitor of its oligomerization, VBIT-4, in the primary culture of mouse lung endotheliocytes and downregulated expression of VDAC1 in human skin fibroblasts on the progression of mitochondrial dysfunction upon hyperglycemic stress. The cells were grown in high-glucose media (30 mM) for 36 h. In response to hyperglycemia, the mRNA level of VDAC1 increased in endotheliocytes and decreased in human skin fibroblasts. Hyperglycemia induced overproduction of mitochondrial ROS, an increase in the susceptibility of the organelles to mitochondrial permeability transition (MPT) pore opening and a drop in mitochondrial membrane potential, which was accompanied by a decrease in cell viability in both cultures. Treatment of endotheliocytes with 5 µM VBIT-4 abolished the hyperglycemia-induced increase in susceptibility to spontaneous opening of the MPT pore and ROS generation in mitochondria. Silencing of VDAC1 expression in human skin fibroblasts exposed to high glucose led to a less pronounced manifestation of all the signs of damage to mitochondria. Our data identify a mitochondria-related response to pharmacological and genetic suppression of VDAC activity in vascular cells in hyperglycemia and suggest the potential therapeutic value of targeting these channels for the treatment of diabetic vasculopathies.